Is the Language Faculty Non Linguistic? - Umberto Ansaldo (Frontiers Research Topics, 2016)
A line of research in cognitive science over several decades has been dedicated to finding an innate, language-specific cognitive system, a faculty which allows human infants to acquire languages natively without formal instruction and within short periods of time. In recent years, this search has attracted significant controversy in cognitive science generally, and in the language sciences specifically. Some maintain that the search has had meaningful results, though there are different views as to what the findings are: ranging from the view that there is a rich and rather specific set of principles, to the idea that the contents of the language faculty are - while specifiable - in fact extremely minimal. But other researchers rigorously oppose the continuation of this search, arguing that decades of effort have turned up nothing. The fact remains that the proposal of a language-specific faculty was made for a good reason, namely as an attempt to solve the vexing puzzle of language in our species. Much work has been developing to address this, and specifically, to look for ways to characterize the language faculty as an emergent phenomenon; i.e., not as a dedicated, language-specific system, but as the emergent outcome of a set of uniquely human but not specifically linguistic factors, in combination. A number of theoretical and empirical approaches are being developed in order to account for the great puzzles of language - language processing, language usage, language acquisition, the nature of grammar, and language change and diversification. This research topic aims at reviewing and exploring these recent developments and establishing bridges between these young frameworks, as well as with the traditions that have come before. The goal of this Research Topic is to focus on current developments in what many regard as a paradigm shift in the language sciences. In this Research Topic, we want to ask: If current explicit proposals for an innate, dedicated faculty for language are not supported by data or arguments, how can we solve the problems that UG was proposed to solve? Is it possible to solve the puzzles of language in our species with an appeal to causes that are not specifically linguistic?